Phototropin phosphorylation of ROOT PHOTOTROPISM 2 and its role in mediating phototropism, leaf positioning, and chloroplast accumulation movement in Arabidopsis. (7th March 2023) - Waksman, Thomas; Suetsugu, Noriyuki; Hermanowicz, Pawel; Ronald, James; Sullivan, Stuart; Łabuz, Justyna; Christie, John M.
SUMMARY: Directional movements impact the ability of plants to respond and adjust their growth accordingly to the prevailing light environment. The plasma‐membrane associated protein, ROOT PHOTOTROPISM 2 (RPT2) is a key signalling component involved in chloroplast accumulation movement, leaf positioning, and phototropism, all of which are regulated redundantly by the ultraviolet/blue light‐activated AGC kinases phototropin 1 and 2 (phot1 and phot2). We recently demonstrated that members of the NON‐PHOTOTROPIC HYPOCOTYL 3 (NPH3)/RPT2‐like (NRL) family in Arabidopsis thaliana, including RPT2, are directly phosphorylated by phot1. However, whether RPT2 is a substrate for phot2, and the biological significance of phot phosphorylation of RPT2 remains to be determined. Here, we show that RPT2 is phosphorylated by both phot1 and phot2 at a conserved serine residue (S591) within the C‐terminal region of the protein. Blue light triggered the association of 14‐3‐3 proteins with RPT2 consistent with S591 acting as a 14‐3‐3 binding site. Mutation of S591 had no effect on the plasma membrane localization of RPT2 but reduced its functionality for leaf positioning and phototropism. Moreover, our findings indicate that S591 phosphorylation within the C‐terminus of RPT2 is required for chloroplast accumulation movement to low level blue light. Taken together, these findings further highlight the importance of the C‐terminal region of NRL proteins and how its phosphorylation contributes to phot receptor signalling in plants. Significance Statement: ROOT PHOTOTROPISM 2 (RPT2) is a key signalling component involved in chloroplast accumulation movement, leaf positioning, and phototropism, which are regulated by phototropin receptor kinases (phot1 and phot2). Here we demonstrate that RPT2 is phosphorylated by phot1 and phot2 at S591 within the C‐terminus and phosphorylation of this residue plays a role in establishing phototropism, leaf positioning and is functionally required for RPT2 to mediate chloroplast movement to low levels of blue light.